Onset, Maintenance, and Cessation of Effect of Galcanezumab for Prevention of Migraine: A Narrative Review of Three Randomized Placebo-Controlled Trials - Kuruppu, Dulanji K.; North, James M.; Kovacik, Amy J.; Dong, Yan; Pearlman, Eric M.; Hutchinson, Susan L. (Advances in therapy, 2021)
Introduction Galcanezumab, a humanized monoclonal antibody that binds to calcitonin gene-related peptide, is approved for the preventive treatment of migraine in adults. It is self-administered once monthly as a subcutaneous injection. This paper describes the time course of effect of galcanezumab in patients with episodic and chronic migraine. Methods Data were based on three double-blind, placebo-controlled, phase 3 studies. Patients (1773 episodic and 1113 chronic) were randomized (2:1:1) to monthly doses of placebo, galcanezumab 120 mg with a 240 mg loading dose, or galcanezumab 240 mg (January 2016–March 2017). Onset of effect was determined using a sequential analysis approach based on earliest time point at which galcanezumab achieved and subsequently maintained statistical superiority to placebo. Maintenance of effect was a comparison of the percentages of galcanezumab- and placebo-treated patients with maintenance of at least 50% response at the individual patient level. Cessation of effect was determined during a 4-month post-treatment period on the basis of change from baseline in monthly migraine headache days. Results Galcanezumab led to a lower percentage of patients who had a migraine headache on the first day after injection, provided maintenance of effect throughout the duration of the double-blind treatment period, and gradually lost effect without signs of rebound headache throughout the post-treatment period in most patients with episodic and chronic migraine. Conclusion Galcanezumab is a novel preventive therapeutic option for adult patients with migraine that has early onset of action, maintenance of effect, and gradual reduction of effect upon treatment cessation. Trial Registration ClinicalTrials.gov: NCT02614183 (EVOLVE-1); NCT02614196 (EVOLVE-2); NCT02614261 (REGAIN).